POTENSI DEMAND TERHADAP PENGEMBANGAN KANAL JONGAYA & PANAMPU SEBAGAI MODA TRANSPORTASI (WATERWAY) DI KOTA MAKASSAR - Fisu, Amiruddin Akbar (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2016)
One of the potential that can be used to solve the congestion problem that occurred in the city of Makassar is by utilizing channels as urban transport medium. Makassar City has three channels with an overall length of 15.11 km, which two of them can be used as a water transport medium. The channels consist of Jongayya Channel (7.83 km), and Panampu Channel (4.92 km). Channel transportation can be one solution to reduce the congestion problems that occurred in the city of Makassar. The purpose of this study is to determine demand potential of waterwa y-based transport modes on Channel Panampu and Jongaya, factors that affect the willingness to use channel as a transportation medium, to identify user preferences related to channel planning as a transportation medium, and to identify the extent to which the role of the channel to become alternative transportation medium. To achieve these objectives, this study used a descriptive-quantitative methods approach. And were subsequently used crosstab analysis method, multinomial logistic regression and approach with stated preference methods.